2018
DOI: 10.5487/tr.2018.34.1.055
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic Oral Dose Toxicity Study ofEnterococcus Faecalis2001 (EF 2001) in Mice

Abstract: As a part of general toxicity studies of Enterococcus Faecalis 2001 (EF 2001) prepared using heat-treatment bacillus mort body EF 2001 in mice, this study examined the toxicity of EF 2001 in single and repeated administrations following the previous report in order to apply this product to preventive medicine. The safety of oral ingestion of EF 2001 was examined in 6-week-old male and female ICR mice with 1,000 mg/kg, 3,000 mg/kg and 5,000 mg/kg body weight/day administrated by gavage of the maximum acceptable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In addition, macrophages activate NK and LAK cells. Thus, in white blood cells, lymphocytes distinguish between self and non-self, give instructions, and play a central role in the immune response [15][16][17][18][19]. In this study, in the non-irradiated group, the β-glucan group showed an increase in the number of lymphocytes, suggesting an increase in the overall white blood cell count.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In addition, macrophages activate NK and LAK cells. Thus, in white blood cells, lymphocytes distinguish between self and non-self, give instructions, and play a central role in the immune response [15][16][17][18][19]. In this study, in the non-irradiated group, the β-glucan group showed an increase in the number of lymphocytes, suggesting an increase in the overall white blood cell count.…”
Section: Discussionmentioning
confidence: 56%
“…It has been reported that the number of granulocytes increases in response to Petrchenko et al Β-(1-3)-D-glucan. Treatment with β-(1-6)-D-glucan has also been reported to cause macrophage activation, increased T cells, and increased TNF-α and IL-release 8 macrophage activation [16][17][18]. However, intraperitoneal administration of these polysaccharides has also been reported to induce inflammation in the peritoneal cavity due to difficulty in intestinal absorption [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Heat-killed E. faecalis was reported to have a radioprotective effect and antitumor activity in vivo. 21,22 Recently, heat-killed E. faecalis EF-2001 (EF-2001) ameliorated atopic dermatitis and inflammatory bowel disease in murine model due to its immunomodulatory effect, 18,23 implying that EF-2001 may be developed to a potential strategy in treatment for inflammatory diseases. However, to our knowledge, direct evidence for the effect of EF-2001 on EtOHinduced acute gastric ulcer has not been elucidated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Enterococcus is a genus of Gram-positive, non-sporeforming bacteria that are frequently found in the oral cavity, gastrointestinal tract, and vagina (Jett et al, 1994). Although most Enterococcus species are considered to be commensal in humans and animals (Gu et al, 2018), Enterococcus faecalis can act as an opportunistic pathogen causing bacteremia, meningitis, endocarditis, or urinary tract-and wound-related infections (Arias et al, 2010;Weiner et al, 2016). In humans, E. faecalis has been predominantly detected in the root canals of patients with post-treatment apical periodontitis or refractory apical periodontitis, suggesting an etiological role in progression of these diseases (Souto and Colombo, 2008;Vidana et al, 2011).…”
Section: Introductionmentioning
confidence: 99%